THE PHYTOCHEMICAL AND PHARMACOLOGICAL PROPERTIES OF CORDIA DICHTOMA: A REVIEW (AYUSHDHARA, 2015)
Sleshamatak (Cordia dichtoma) is a medicinal plant explained in Ayurvedic literature and in modern science too. Cordia dichotoma is a plant species in the genus Cordia. The genus Cordia, with about 300 identified species and worldwide distribution, is one of the largest genera in the family boraginaceae.Cordia dichtoma commonly known as Lasoda, has number of therapeutic properties. Cordia dichtoma is also known as Shleshmatak, Shelu, Clammy Cherry, Indian Cherry, Sebesten. The plant contains cathartin, allantoin, β-sitosterol, palmitic acid, linoleic acids, pyrrolizidine alkaloids, coumarins, flavonoids, saponins, terpenes and sterols. In Ayurvedic texts Lasoda is considered as a snehopaga and single used drug for all types of Gastro-intestinal disorders thoroughly internal and external mode. Cordia has long been used in traditional medicine for cicatrizant, astringent, anti-inflammatory, anthelminthic, antimalarial, diuretic, febrifuge, appetite suppressant, cough suppressant and to treat urinary infections, lung diseases and leprosy. There are so many researches has been done on this plant like Anti-ulcer activity, Anti-diabetic, wound healing, contraceptive effect, Hepato-protective, Anti-microbial, Anti-inflammatory and Anthelmintic. This review represents brief information about botanical description, chemical constituents, and functional as well as medicinal uses of Cordia dichtoma. The plant also has number of pharmaceutical applications i.e. may be used as excipient in many of indigenous formulations. This review will definitely give the helpful information about this plant.